ARTICLE 25 INCOME TAX ASPECTS OF TAXPAYER UNDER CERTAIN EMPLOYERS LAW 36 OF 2008 (Entrepreneur, 2012)
Abstract The business world is now experiencing a very rapid progress. Among other factors affecting the opening lines of international trade, technological sophistication, a more flexible business rules to be triggered by a change in consumption patterns. Indonesia is also experiencing a change in the business world in the country is experiencing significant growth, particularly the real sector. thriving outlets, shops, kiosks, cafes, grocery store or mini seiiring with the rapid growth of shopping malls such as, mall, shopping center, where the longer growing numbers. Types of goods sold even more diverse. Various reasons that makes people to be involved in the business world, such as ease of starting, does not require a large capital and specialized expertise, vast place, to ease in matters of taxation. Perpetrators in the business of trading is commonly referred to as retail traders. In the context of income tax, the scope of the retailers provided for in Article 1 of Regulation Number 2 Director General of Taxation (DG) Tax Number PER-32/PJ./2010, which is an individual retailers who make sales of goods either wholesale or retail and delivery services through a place. In tax treatment, as retailers attach individual taxpayer Specific Employers (WPOPPT). Use of designation